2013
DOI: 10.9755/ejfa.v25i9.16393
|View full text |Cite
|
Sign up to set email alerts
|

Invasive species may offer advanced phytoremediation of endocrine<br>disrupting chemicals in aquatic ecosystems

Abstract: One of the major areas of advancement in environmental science is bioremediation. Researchers have been using bacteria, fungi, algae and now macrophytes to remove pollutants from aquatic and terrestrial ecosystems. Here we share the results of a study on the macrophyte uptake of xenoestrogens from an urban river. We found that the invasive curly leaf pond weed (Potamogeton illinoensis) accumulated an average of 66% higher levels of estrogenic compounds and 94% more Bisphenol-A than the native Illinois pondweed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Plants were sampled in only 11 studies across all continents, where the low sampling efforts may be due to their ability to accumulate EDCs but at different rates depending on the species. For example, the invasive curly leaf pond weed (Potamogeton illinoensis) has demonstrated greater accumulation of estrogenic compounds (averaging 66%) and bisphenol A (94%) than a native pondweed (Trueman & Erber, 2013).…”
Section: Differences In Edcs and Sample Types Studiedmentioning
confidence: 99%
“…Plants were sampled in only 11 studies across all continents, where the low sampling efforts may be due to their ability to accumulate EDCs but at different rates depending on the species. For example, the invasive curly leaf pond weed (Potamogeton illinoensis) has demonstrated greater accumulation of estrogenic compounds (averaging 66%) and bisphenol A (94%) than a native pondweed (Trueman & Erber, 2013).…”
Section: Differences In Edcs and Sample Types Studiedmentioning
confidence: 99%
“…Ailanthus altissima (Mill.) Swingle China [19,89,90] Potamogeton illinoensis Morong North America [91,92] Artemisia vulgaris L. Euroasia [93,94] Bioenergy Panicum virgatum L. Central and Eastern USA [26][27][28] Arundo donax L. Euroasia [95,96] Paulownia tomentosa (Thunb.) Steud.…”
Section: Reducing Environmental Pollution and Phytoremediationmentioning
confidence: 99%
“…Plant uptake and metabolism of hydrophobic organic compounds is presented as less important than microbial degradation, as afore-mentioned in this manuscript. However, uptake of BPA in plant tissues or metabolization into other compounds with less endocrine-disrupting activity, has been indicated in several research studies (Lu et al, 2015;Dodgen et al, 2013;Trueman and Erber, 2013) and could be suggested as a possible pathway in this experiment, even of lesser importance.…”
Section: Cw With Halophytes For the Degradation Of Bpa In Primarytreated Municipal Wastewatermentioning
confidence: 86%